Facing the challenges in structural engineering : proceedings of the 1st GeoMEast International Congress and Exhibition, Egypt 2017, on sustainable civil infrastructures /: proceedings of the 1st GeoMEast International Congress and Exhibition, Egypt 2017, on sustainable civil infrastructures. ([2018]) - Unknown
No abstract available